2012
DOI: 10.2140/involve.2012.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Elliptic curves, eta-quotients and hypergeometric functions

Abstract: Abstract. The well-known fact that all elliptic curves are modular, proven by Wiles, Taylor, Breuil, Conrad and Diamond, leaves open the question whether there exists a 'nice' representation of the modular form associated to each elliptic curve. Here we provide explicit representations of the modular forms associated to certain Legendre form elliptic curves 2 E 1 (λ) as linear combinations of quotients of Dedekind's eta-function. We also give congruences for some of the modular forms' coefficients in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…127, Entry 7.30]. The identification of L(E 33 , 2) in terms of F (1,11) and F (3,11), follows from integrating the associated cusp form [17].…”
Section: Telescoping Modular Equations and Numerical Conjecturesmentioning
confidence: 99%
“…127, Entry 7.30]. The identification of L(E 33 , 2) in terms of F (1,11) and F (3,11), follows from integrating the associated cusp form [17].…”
Section: Telescoping Modular Equations and Numerical Conjecturesmentioning
confidence: 99%
“…It is natural to ask when elliptic curves are associated to modular forms that can be written as linear combinationa of eta-quotients. Recently, Pathakjee, RosnBrick, and Toong [22] demonstrated four such examples, utilizing spaces of cusp forms which are spanned by eta-quotients. Further work on when spaces of modular forms are spanned by eta-quotients has been done by Rouse and Webb [23], Arnold-Roksandich, James, and Keaton [3], and Kilford [10], for example.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…if (p, q) ≡ (5, 5) (mod 24). However, neither (22) nor (23) have nonnegative integer solutions which satisfy (21), which is a contradiction. Thus we have shown that there are no eta-quotients in M 2 (Γ 1 (pq)) for (p, q) ≡ (1, 5), (5, 1), (5, 5) (mod 24) and p, q > 5.…”
Section: Eta-quotients Of Semiprime and Squarefree Levelmentioning
confidence: 97%
See 1 more Smart Citation
“…and Ono[49] listed all the weight 2 newforms that are eta quotients, and gave their corresponding strong Weil curves. There are such eta quotients only for M 2 (Γ 0 (N )) with N = 11, 14, 15, 20, 24, 27, 32, 36, 48, 64, 80, 144.Recently in[59], newforms in M 2 (Γ 0 (N )) with N = 33, 40, 42, 70 are given as linear combinations of eta quotients. In[2], congruences between Fourier coefficients of some newforms is given.…”
mentioning
confidence: 99%